DAKWAH ISLAM DI ERA MILLENIAL (Studi Pengajian Gus Iqdam Pada Majelis Ta’lim Sabilut Taubah) - Najib, Muhammad Fikri ‘Ainun (Civiliza Publishing, 2023)
Da'wah is the duty of all people. Now da'wah millennial is no longer hindered by space and time, because it can be conveyed and received wherever it is. Technology also influences da'wah activities, one of which is da'wah through social media. One of the media that has developed very rapidly and is favored by mad'u is YouTube, so it is interesting for researchers to conduct a da'wah research using social media. Choosing the da'wah carried out by Gus Iqdam is a research, because he is currently very popular with many people, especially young people. His relaxed and easy-to-understand style, which is synonymous with the Javanese language, made his congregation grow. Of course, this cannot be separated from the social media they have. One that is used is YouTube media with the Gus Iqdam Official channel. By utilizing the YouTube media so that anyone and anywhere mad'u can follow his studies.